Structural performance of Kolej Kediaman Tun Mustapha due to earthquake - Noell Ibrahim Fred (2022)
The majority of buildings constructed in Sabah are reinforced concrete structures. These existing buildings are designed according to the British Standard code of Practice (BS8110) without the consideration of seismic provisions. Consequently, this makes the existing building susceptible to potential seismic hazards. This research focuses on the Blok M (4-storey and 3-storey) of Kolej Kediaman Tun Mustapha in Universiti Malaysia Sabah, Kota Kinabalu. PROTA software was utilized to develop the models of the Blok M buildings. Response spectrum method was performed to obtain lateral displacements of storey for both buildings. The Interstorey Drift Ratio (%) was calculated based on the storey displacement and the performance level is evaluated based on FEMA 346 (2000). The lateral displacement was directly proportional to the height of the buildings. structural performance levels of KKTM residential buildings were determined as Immediate Occupancy (IO) where it is determined to be safe to use after an earthquake.